Effects of different sulfuric acid etching concentrations on PEEK surface bonding to resin composite - Pisaisit Chaijareenont (2018)
© 2018, Japanese Society for Dental Materials and Devices. All rights reserved. This study evaluated the effects of surface pretreatment with different concentrations of sulfuric acid etching on surface properties and bonding between Polyetheretherketone (PEEK) and a resin composite. Six groups of surface pretreatment (no pretreatment, etched with 70, 80, 85, 90, and 98% sulfuric acid for 60 s) were treated on PEEK. Surface roughness, scanning electron microscopy (SEM) and atomic force microscopy (AFM) analyses were examined. Shear bond strength (SBS) and cross-sectional observations of the interfaces were performed. One-way ANOVA analysis revealed differences in surface roughness and SBS between groups. The 90 and 98% sulfuric acid etching significantly achieved the highest SBS (p<0.05). SEM and AFM demonstrated etched surfaces with wide and deep pores. The 90 and 98% sulfuric acid etching were suggested to be the optimal concentration to improve adhesion between PEEK and the resin composite.